Osteoid Osteoma of the Proximal Fibula: An Uncommon Location with the Indication for Open Surgery. (22nd December 2011) - Marquass, Bastian; Hepp, Pierre; Theopold, Jan Dirk; von Dercks, Nikolaus; Blattert, Thomas R.; Josten, Christoph
Abstract : Purpose . This is a case report of a patient with an osteoid osteoma of the proximal fibula. The objective is to illustrate a rare tumor location that requires open surgery due to closeness of neurological structures. Methods . Clinical and roentgenographic findings, treatment, and histological appearance are presented. Results . Local pain and swelling of the proximal fibula with improvement under salicylates led to the diagnosis of an osteoid osteoma, what was confirmed with an MRI scan. Due to proximity to the common peroneal nerve, we decided for open surgery. During the operation, the nerve was seen to cross the tumor site making it necessary to retract it to expose the entire tumor. Histologically, typical features of osteoid osteoma with a rather well-defined nidus surrounded by sclerotic bone were seen. A complete removal was performed. Conclusion . Osteoid osteomas of the proximal fibula are rare. When planning surgery, the common peroneal nerve must be identified, and its further distal course should be taken into account to avoid iatrogenic damage to the nerve.